Elasticity and cross-sectional thickness of paraspinal muscles in progressive adolescent idiopathic scoliosis - Fan, Yunli; Zheng, Haiping; Feng, Lin; To, Michael K. T.; Kuang, Guan-Ming; Yeung, Eric H. K.; Cheung, Kenneth M. C.; Liu, Li; Cheung, Jason P. Y. (Frontiers in Pediatrics, 2024)
(1) Compare the cross-sectional thickness (CST) and shear wave speed (SWS) of paraspinal muscles (PSM) in adolescent idiopathic scoliosis (AIS) with and without curve progression; (2) investigate the relationship between CST/SWS and radiographic characteristics in AIS with curve progression; (3) compare the CST/SWS between AIS and non-scoliosis controls.This cross-sectional study analyzed the CST and SWS of PSM in 48 AIS with mild to moderate curvature and 24 non-scoliosis participants. Participants with scoliosis greater than 45° of Cobb angles were excluded. The Change of Cobb angles within the last 6-months was retrieved to allocate AIS into progression and non-progression groups. The SWS and CST of multifidus; longissimus and iliocostalis of the major curve were measured using B-mode ultrasound image with an elastography mode. Discrepancies of the SWS (SWS-ratio: SWS on the convex side divided by SWS on the concave side) and CST (CST-ratio: CST on the convex side divided by CST on the concave side) at the upper/lower end and apical vertebrae were studied.Results: A higher SWS at the apical vertebrae on the concave side of the major curve (multifidus: 3.9±1.0m/s vs 3.1±0.6m/s; p<0.01, longissimus: 3.3±1.0m/s vs 3.0±0.9m/s; p<0.01, iliocostalis: 2.8±1.0m/s vs 2.5±0.8m/s; p<0.01) was observed in AIS with curve progression. A lower SWS-ratio at apical vertebrae was detected with a greater vertebral rotation in participants with curve progression (multifidus [grade II]: 0.7±0.1 vs grade I: 0.9±0.2; p=0.03, longissimus [grade II]: 0.8±0.2 vs grade I: 1.1±0.2; p<0.01). CST was not different among the progressive, non-progressive AIS and non-scoliosis controls.Conclusions: Increased SWS of PSM without change of CST was observed on the concave side of the major curve in participants with progressive AIS.